Asian university students’ perspectives on online English courses during COVID-19: A systematic review - Nurzahirah Zainal; Melor Md Yunus (Institute of Advanced Engineering and Science, 2022)
Globally, English courses intended for university students are conducted online due to the COVID-19, including in Asian countries. Hence, this systematic review paper attempts to review relevant studies regarding the Asian university students’ perspectives towards online English courses during COVID-19. This paper employs PRISMA, whereby several stages to filter and gather relevant information have been carried out. Twelve articles have been identified and analysed based on the research designs, methodologies, and themes. The main themes are positive and negative perspectives on online English courses learning during COVID-19, and suggestions to improve online English courses learning during COVID-19. It is found that university students in Asia are generally ready to learn online English courses due to flexibility and easy access. Poor internet connection and infrastructure are among negative perspectives towards the online English courses during COVID-19. It is recommended that improving technological infrastructure, conducting training programmes, and restructuring task assessments should be done to improve the quality of online English courses during COVID-19.